2014
DOI: 10.3390/rs6032108
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Gross Primary Productivity Derived from GIMMS NDVI3g, GIMMS, and MODIS in Southeast Asia

Abstract: Gross primary production (GPP) plays an important role in the net ecosystem exchange of CO 2 between the atmosphere and terrestrial ecosystems. It is particularly important to monitor GPP in Southeast Asia because of increasing rates of tropical forest OPEN ACCESSRemote Sens. 2014, 6 2109 degradation and deforestation in the region in recent decades. The newly available, improved, third generation Normalized Difference Vegetation Index (NDVI3g) from the Global Inventory Modelling and Mapping Studies (GIMMS) gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(31 citation statements)
references
References 78 publications
2
28
0
Order By: Relevance
“…Previous studies showed the ability of GIMMS3g to capture productivity dynamics (Wang et al 2014, Zhu & Southworth 2013. Our result of NDVI increasing trends is in agreement with the increase in carbon storage observed for African intact tropical forests ), as well as with the increase in net primary production recorded at a global scale (Nemani et al 2003).…”
Section: Regional Forest Productivity and Climate Variable Trendssupporting
confidence: 79%
“…Previous studies showed the ability of GIMMS3g to capture productivity dynamics (Wang et al 2014, Zhu & Southworth 2013. Our result of NDVI increasing trends is in agreement with the increase in carbon storage observed for African intact tropical forests ), as well as with the increase in net primary production recorded at a global scale (Nemani et al 2003).…”
Section: Regional Forest Productivity and Climate Variable Trendssupporting
confidence: 79%
“…It is a proxy for vegetation productivity of the terrestrial ecosystem [15,16]. The GIMMS (Global Inventory Modeling and Mapping Studies) 15-day composite NDVI3g dataset applied here has been shown to be more accurate than the GIMMS NDVI for monitoring vegetation activity and phonological change [17][18][19]. Its spatial resolution is 8 km.…”
Section: Datasetsmentioning
confidence: 99%
“…Therefore, we suggest that the uncertainty of climatic factors has little impact on MOD17. However, FPAR, as a key forcing variable of remote sensing, has a large uncertainty owing to the data qualities, thus it may be an important reason for underestimated peak values of GPP_EC [31][32][33][34]. Additionally, FPAR is derived from MODIS NDVI, which is sensitive to canopy background variations and saturates in areas with dense tree canopy, especially in the growing season [35,36].…”
Section: Uncertainties Errors and Accuraciesmentioning
confidence: 99%